Assessment of Neurokinin B and Galanin Levels in Women with Polycystic Ovarian Syndrome - Malik, Maryam A.; Alsaffar, Sura F. (Iraqi Journal of Science, 2025)
Polycystic ovarian syndrome (PCOS) is a common endocrine disorder that predominantly affects women of reproductive age, impacting their hormonal balance and fertility. The present study was conducted to evaluate the levels of neurokinin B and galanin in women with PCOS. The study recruited PCOS patients who visited infertility consultation at the Medical City of Baghdad Hospital, Baghdad, Iraq. Patients were categorized into two groups based on their body mass index (BMI): thirty healthy control women, whose average age was between 20 and 35 years, and sixty PCOS patients, who were overweight group (BMI less than 30 kg/m2) or obese group (BMI more than 30 kg/m2). The diagnosis of PCOS in women was based on the presence of at least two of the three characteristic criteria: hyperandrogenism, oligo- or anovulation, and polycystic ovaries. Weight measurements were recorded in kg, while height, waist, and wrist circumferences were recorded in cm. Serum samples were obtained from women with PCOS and a control group during the early follicular phase. The neurokinin B, galanin, anti-mullerian hormone (AMH), and testosterone levels in the blood samples were determined. The results indicated that galanin levels were higher in PCOS patients in both groups. The PCOS patients showed a significant increase in neurokinin B levels in the obese group, and there was a positive correlation between neurokinin B and wrist circumference in the same group. However, this elevation was not statistically significant. The group that was obese had significantly higher levels of AMH and testosterone. In the group of obese patients, there was also a positive correlation with waist circumference. The results of the present study revealed that neuropeptides (neurokinin B and galanin) were elevated in obese PCOS patients, which confirms the positive correlation between obesity and PCOS incidence. neuropeptide (neurokinin b and galanin) was elevated in obese PCOS patient that confirm the positive correlation between obesity and PCOS incidence.